2005
DOI: 10.1111/j.1574-0864.2005.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Hired labor use decisions in cassava‐producing households of sub‐Saharan Africa

Abstract: Sub-Saharan Africa is the only developing region of the world where agricultural output has been trailing population growth for most of the last three decades. Farming systems in the region are inherently risky because they are fundamentally dependent on the vagaries of weather. In addition, it is a region of crises; poverty, civil strife, and HIV/AIDS. Attention must therefore be focused on improving the production of crops that could thrive under these circumstances. Because of its tolerance of extreme droug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
2
10
1
Order By: Relevance
“…Hence, this type of market could be said to be uncompetitive because individual marketers especially company agents had great influence on the market price. This did not agree with the work of Enete (2003) in cassava marketing in Nigeria, Enete and Agbugba (2008) in Charcoal marketing in Abia State and Hayami et al (1999) in rice marketing in Philippines. A high Gini coefficient of 0.68 was obtained by Ike and Chukwuji (2005) which implied that there was significant inequality in the distribution of income among the cashew nut sellers and hence, a high level of concentration.…”
Section: Gini Coefficient For Market Participantscontrasting
confidence: 41%
“…Hence, this type of market could be said to be uncompetitive because individual marketers especially company agents had great influence on the market price. This did not agree with the work of Enete (2003) in cassava marketing in Nigeria, Enete and Agbugba (2008) in Charcoal marketing in Abia State and Hayami et al (1999) in rice marketing in Philippines. A high Gini coefficient of 0.68 was obtained by Ike and Chukwuji (2005) which implied that there was significant inequality in the distribution of income among the cashew nut sellers and hence, a high level of concentration.…”
Section: Gini Coefficient For Market Participantscontrasting
confidence: 41%
“…This type of market structure is competitive, because the individual agents have little or no influence on the market price. Nweke et al (2002), Enete (2003), and Haggblade (2012), have made similar observations with cassava in Nigeria and several countries in sub-Saharan Africa where the commodity is traded within a perfectly competitive market structure featuring large number of suppliers and buyers of a homogenous product. Akinpelu and Adenegan (2011) and Ugwumba, Okoh and Uzuegbunam (2011) have also conducted price-concentration studies for the sweet potato and live-catfish markets in Anambra and Abia States of Nigeria, respectively.…”
Section: Structure Of Wood Charcoal Marketmentioning
confidence: 49%
“…Enete (2003) reported marketing margin of 50% for fresh cassava root in Nigeria. Goossens (1996) observed that margins can be as high as 45% for cassava products in Democratic Republic of Congo (DRC).…”
Section: Marketing Cost and Marginmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the average household education level of middle school/JSS or lower is expected to exert a negative effect on the farmer's demand for hired labour. Enete et al (2005) estimated a Tobit model for hired labour and found out that the characteristics of the household head (age and number of years of formal education), the size of the household farm, good market access, and population pressure motivate households to apply hired labour in cassava production. Also, Benjamin and Kimhi (2006) from an estimated multinomial model reported that hired farm labour increases with the farmer's qualifications, perhaps substituting for the couple's labour inputs while other adults in the household substitute for the farm labour input of the farm couple and hired workers.…”
Section: Measuring the Hired Labour Demand Functionmentioning
confidence: 99%